COMPONENT ANALYSIS AT FORT KEDUNG COWEK BUILDINGS IN SURABAYA, EAST JAVA: OBSERVATION ON PANOPTICON CONCEPT - Giffari, Rafli Ahmad (International Review of Humanities Studies, 2021)
The fortress in the 20th century has certain characteristics to match the war strategy that is applied at this time. In 1900 the Kustbatterij Kedoeng-Tjowek project or Kedung Cowek fortress was built as a coastal defense for the city of Surabaya by the Dutch colonial. This study aims to identify the function of each building contained in the Kedung Cowek fort military area using a component review by their availability and categorization. Based on the analysis results it is known that each building has a specific function related to the concept of panopticon to apply the value of surveillance in its defense system.